Pengaruh motivation dan organizational commitment terhadap employee performance - Wijaya, Bryan Satrio; Frianto, Agus (Universitas Negeri Surabaya, 2024)
This research aims to determine the influence of motivation and organisational commitment on employee performance. The research location in this study was carried out at BPJS Employment Karimunjawa Surabaya. This research uses quantitative research. The primary and secondary data sources used in this research are primary and secondary. In this research, a questionnaire was used as a data collection technique. The sampling method in this research used a saturated sampling technique with 33 respondents from BPJS Employment Karimunjawa Surabaya. The data analysis technique is a regression with Statistical Product and Service Solutions (SPSS) software version 29. The research results show that motivation has a significant effect on employee performance, while the organisational commitment variable also has a large effect on employee performance. Apart from that, the research results also prove that motivation and organisational commitment have a substantial effect on employee performance. The implication of this research is the need for good motivation and organisational commitment for employees to improve employee performance and create stable and increasing employee performance.